2′, 4′-Dihydroxy-6′-methoxy-3′, 5′-dimethylchalcone induced apoptosis and G1 cell cycle arrest through PI3K/AKT pathway in BEL-7402/5-FU cells. (September 2019) - Ji, Xiang; Wei, Xing; Qian, Jie; Mo, Xuejun; Kai, Guoyin; An, Faliang; Lu, Yanhua
Abstract: Hepatocellular carcinoma is the fifth most common and the third most lethal cancer worldwide. In recent years, natural flavonoids have drawn great attention as repository for the exploitation of novel antineoplastic agents. 2′, 4′-Dihydroxy-6′-methoxy-3′, 5′-dimethylchalcone (DMC), a functional chalcone isolated from the buds of Cleistocalyx operculatus, has been reported to exert potent cytotoxicity against multi-drug resistant BEL-7402/5-FU cells. In this study, the precise mechanisms of DMC-mediated growth inhibition in BEL-7402/5-FU cells were further investigated. DMC was found to trigger apoptosis predominantly via the mitochondria-dependent pathway and the enhancement of reactive oxygen species (ROS) generation. Meanwhile, DMC induced G1 cell cycle arrest through downregulation of cyclin D1 and CDK4. Furthermore, DMC increased p53 level and inhibited NF-κB nuclear-localization via suppression of PI3K/AKT signaling axis, which might be the underlying mechanism of DMC-induced apoptosis and cell cycle arrest in BEL-7402/5-FU cells. Collectively, the study elucidated the mechanisms by which DMC may inhibit the growth of BEL-7402/5-FU cells and suggested the possibility that DMC might be a promising candidate therapeutic agent for hepatoma treatment in the future. Graphical abstract: Image 1 Highlights: This paper explored the molecular mechanisms underlying the inhibitory effect of DMC on BEL-7402/5-FU cells. DMC induced apoptosis via mitochondria-dependent pathway in BEL-7402/5-FU cells. DMC blocked cell cycle progression at G1 phase by regulating the level of cyclin D1, CDK4, p21 and GSK3β. DMC increased p53 level and inhibited NF-κB nuclear-localization via suppression of PI3K/AKT pathway.